The Accuracy of Food and Drink Cards As A Tool For Estimating Total Nutrients And Calories Intake - Ardesy Melizah Kurniati; Arisman; Minerva Riani Kadir (Fakultas Kedokteran Universitas Sriwijaya, 2019)
nterview method in exploring foods and drinks intake require estimation tool. Household measuring instruments can be used, as well as of food photographs and three-dimension food models. The purpose of this study was to assess the accuracy of food and drink cards as a tool to estimate the portion of real food and drink. A total of 32 respondents participated in this study. Food records were collected thenbody weight and height of respondentswere measured. In the following day, the respondents estimated the portion of the real foods and drinks compare to the cards. Fifty-one cards are considered accurate from the total 67 cards. Food and drink cards can be used as a tool to estimate nutritional intake and total calories.